Soil-plant-animal relationship of copper in milch buffaloes of Jind district in Haryana - Yadav, Sunil; Khirwar, S S (The Indian Journal of Animal Sciences, 2012)
Samples of soils, and feeds and fodders grown on such soils, and milk, blood and hair of 150 milch buffaloes of 10 villages of Jind district of Haryana were collected and analysed for copper content. Diethylene triamine penta acetic acid extractable copper content of soil varied from 0.32 to 1.26 with an average of 0.74±0.02 mg/kg. Average copper content in wheat straw, berseem, sorghum stover, cottonseed- cake and wheat flour were 8.15±0.24, 39.70±1.29, 20.02±0.92; 43.26±0.94 and 26.15±0.65 mg/kg, respectively, Total copper intake of milch buffaloes varied between 187.75 and 629.28 with an average of 389.34±9.17 mg/kg. The composite diet was found to contain an average of 25.42 mg copper kg. Copper content of blood , milk and hair averaged to 0.46±0.06; 0.57±0.20 and 4.04±0.15 mg/kg. Soil copper content had positive correlation (P<0.05) with its content in berseem (+0.20), sorghum stover (+0.16), wheat straw (+0.24) and wheat flour (+0.28). Similarly total copper intake was found to have positive correlation with milk (+0.32) and blood copper (+0.18). These observations showed that copper content of soil was sufficient to meet the needs of plant growth and, therefore, the feedstuffs available in the district were containing sufficient copper to meet the requirement of animals as indicated by normal level of copper in blood and milk of milch buffaloes.